Role of alveolar ridge resorption and occlusal changes in denture instability over time - Manal Bedawi; Abdulaziz Alamri; Hassan Aljarash; Noor Ishwaiheen; Alhassan Alrasheed; Abdulmajeed Alkhalifa; Mamdouh Alsubail; Mohammed Alshehri; Sultan Alqahtani; Essra Alfraih; Ahmed Munshet (International Journal Of Community Medicine And Public Health, 2026)
Complete dentures remain an established treatment for edentulous patients, yet their stability may progressively deteriorate as the oral supporting structures change over time. Residual alveolar ridge resorption is a continuous biological process following tooth loss, characterized by reductions in ridge height, width, and morphology. These changes modify the denture-bearing foundation and gradually reduce the adaptation of the denture base to the underlying tissues. The mandibular ridge is particularly vulnerable to extensive resorption, making lower denture instability a frequent long-term clinical problem. Loss of intimate tissue contact reduces support and resistance to horizontal and rotational displacement, particularly during mastication. Changes in the residual ridge can also modify maxillomandibular relationships and disturb previously established occlusal contacts. Denture settling, artificial tooth wear, tissue displacement, and progressive ridge remodeling may produce premature contacts and occlusal interferences that generate unfavorable lateral or tipping forces. The interaction between reduced anatomical support and altered occlusion can therefore accelerate functional deterioration of an otherwise satisfactory prosthesis. Clinically, persistent instability may be presented as impaired mastication, reduced bite force, mucosal soreness, difficulty during speech, food avoidance, and decreased confidence while wearing dentures. These effects may negatively influence patient satisfaction, dietary choices, social functioning, and oral health-related quality of life. Long-term management requires periodic assessment of residual ridge morphology, denture base adaptation, border extension, occlusal relationships, tissue health, and functional movement of the prosthesis. Occlusal adjustment and clinical remount procedures may correct discrepancies, while relining or rebasing can restore adaptation when tissue changes have compromised fit. Denture replacement may become necessary when extensive structural or occlusal deterioration is present. For patients with severe mandibular ridge resorption and persistent instability, implant-retained overdentures can provide improved retention and functional stability. Regular prosthodontic maintenance remains essential because anatomical remodeling and prosthetic wear continue throughout denture service.